Anti-inflammatory and/or immunomodulatory activities of Uncaria tomentosa (cat’s claw) extracts: A systematic review and meta-analysis of in vivo studies - Arado, Gustavo Marin; Amatto, Pedro de Padua G.; Marins, Mozart; Rizzi, Elen Sanchez; França, Suzelei de Castro; Coppede, Juliana da Silva; Carmona, Fábio; Pereira, Ana Maria Soares (Frontiers in Pharmacology, 2024)
Background Uncaria tomentosa (Willd. ex Schult.) DC. (Rubiaceae) is traditionally used by Amazonian indigenous groups to treat inflammatory diseases. To date, there are no systematic reviews and meta-analyses on the use of U. tomentosa for inflammation control in animals supporting the traditional knowledge about this species. This study was conducted to evaluate the effect of U. tomentosa extracts in modulating inflammatory mediators and to determine which types of inflammatory diseases can be treated by this species. Methods We conducted a systematic review and meta-analysis of preclinical studies published before 26 July 2023, identified in PubMed, Embase, and Scopus. Four independent reviewers extracted the data and assessed the risks of bias. The effects of U. tomentosa on inflammatory diseases and the inflammatory mediators involved were extracted from the studies. Standardized mean differences (SMD) and 95% confidence intervals (95%CI) of the outcomes were estimated. The meta-analyses were conducted using RevMan 5.4 (Cochrane Collaboration). This protocol was registered in PROSPERO (CRD42023450869). Results Twenty-four of 523 studies were included. U. tomentosa extracts decreased the cytokines interleukin (IL)-6 (SMD: −0.72, 95%CI: −1.15, −0.29, p = 0.001) and transcription factor nuclear factor kappa-B (NF-κB) (SMD: −1.19, 95%CI: −1.89, −0.48, p = 0.001). However, the extracts did not significantly alter IL-1 (SMD: −0.16, 95%CI: −0.87, +0.56, p = 0.67), IL-10 (SMD: −0.05, 95%CI:–0.35, 0.45, p = 0.80), or tumor necrosis factor-alpha (TNF-α) levels (SMD: 0.18, 95%CI: −0.25, 0.62, p = 0.41). Conclusion Many extracts of stem bark, roots, and leaves of U. tomentosa, mostly aqueous and hydroethanolic, exhibited anti-inflammatory and/or immunomodulatory activities and low toxicity. The extracts decreased NF-κB and IL-6. These findings suggest that this species has the potential to treat inflammatory diseases in which these markers are increased, according to the ethnopharmacological use. These activities are not related to a specific class of compounds. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=450869, Identifier CRD42023450869.